EFEK MODERASI SKEPTISISME PROFESIONAL PADA PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA AUDITOR KANTOR AKUNTAN PUBLIK DI PROVINSI BALI - Putra, I Dewa Made Arik Permana; Sintaasih, Desak Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This study a aims to analyze the effect of competence on auditor performance, to analyze the effect of compensation on auditor performance on auditor performance, to analyze the effect of moderation on the e influence of f competence on auditor performance and to analyze the effect of moderation on the influence of compensation on a auditor a performance. This a re search was a conducted at auditor of public accountant office in Bali Province with respondent amount 67 auditor. Methods of f data collection e using survey method e with questionnaire technique.Data analysis e technique use d e moderation regression analysis technique. The results showed that competence has a positive and significant effect on auditor performance, compensation has positive and significant influence on auditor performance. While the effect of moderation on professional skepticism reinforces the influence of competence on the performance of auditors, as well as the moderate effects of professional skepticism reinforces the compensatory effect of auditor performance.